Why our teenagers leave the church: personal stories from a 10-year study - Dudley, Roger L. (Review and Herald Pub. Association, 2000)
Between 40 and 50 per cent of Adventist youth leave the church in their 20s. Why? How can we keep them? How can we win them back? This book is the culmination of a magnificent obsession. For more than ten years Roger Dudley traced the lives of 1500 teenagers as they grew up and, often, grew disillusioned. Refusing to let them leave in peace, Dudley bombarded them with questionnaires. Many of them answered. This is their story. Dudley puts faces on the statistics by focusing in on individual case studies. He cites the heart-wrenching testimony of desperately lonely people surrounded by uncaring members. They want to belong, to be needed, to be heard, to be loved. They made some mistakes. We share their pain and their dreams, and feel the dissonant cadences of their troubled hearts. Some who never left explain what kept them in the church. Many who left want to return. "Without God, life is hell," wrote one. If you want to know what the youth of your church are not telling you, read this book. It includes the responses of a group of kids who were asked to design the ideal church, and an appendix explaining the causes of "adolescent heresy," the conflict spawned by the teenage struggle for autonomy.